Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Beban Kerja dan Kompensasi Terhadap Kinerja Karyawan Lamoist Layer Cakes - Rona Tanjung; Refna Wahyu Nurcahyani; Rahman Hasibuan; Sri Langgeng Ratnasari (Sains: Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the effect of Leadership Style, Work Environment, Workload and Compensation on Employee Performance of Lamoist Layer Cakes. The population is 65 people were all employees of Lamoist Layer using a total sampling technique. Type of research uses quantitative and descriptive analysis research design. Collection data was distributing questionnaires via Google Form. The results of this study indicate that 1) Leadership Style has a positive and significant effect on employee performance 2) Work environment has a positive and significant effect on employee performance 3) Workload has a positive and significant effect on employee performance 4) Compensation have a positive and significant effect on employee performance 5) Leadership Style, Work Environment, Workload and Compensation together have a significant influence on employee performance. This can be seen from the value of F count 60.077 ≥ F table 2.523 with a significant level of 0.000 <0.05.